2005
DOI: 10.1038/labinvest.3700355
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic glioma cells with active glycogen synthase are sensitive to PTEN and inhibitors of PI3K and gluconeogenesis

Abstract: Increased glycolysis is characteristic of malignancy. Previously, with a mitochondrial inhibitor, we demonstrated that glycolytic ATP production was sufficient to support migration of melanoma cells. Recently, we found that glycolytic enzymes were abundant and some were increased in pseudopodia formed by U87 glioma (astrocytoma) cells. In this study, we examined cell migration, adhesion (a step in migration), and Matrigel invasion of U87 and LN229 glioma cells when their mitochondria were inhibited with sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 69 publications
(64 reference statements)
1
95
0
1
Order By: Relevance
“…These two signaling networks earlier were linked to invasive cells within GBMs (13,40,41). Interestingly, the PI3K/Akt pathway is also critically involved in several steps of both anaerobic and aerobic glycolysis regulation, as, for example, in localization of glucose transporters at the cell surface and maintenance of hexokinase function in the absence of extrinsic regulatory factors (40,42,43). Thus, activation of Akt as a result of bev-induced hypoxia may increase intracellular glucose and stimulate anaerobic glycolysis and lactate production, thereby promoting invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These two signaling networks earlier were linked to invasive cells within GBMs (13,40,41). Interestingly, the PI3K/Akt pathway is also critically involved in several steps of both anaerobic and aerobic glycolysis regulation, as, for example, in localization of glucose transporters at the cell surface and maintenance of hexokinase function in the absence of extrinsic regulatory factors (40,42,43). Thus, activation of Akt as a result of bev-induced hypoxia may increase intracellular glucose and stimulate anaerobic glycolysis and lactate production, thereby promoting invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has also been reported that metformin, a well-known biguanide, inhibits cancer cell migration and proliferation, 11 an effect that is enhanced by combination treatment with other anticancer agents. 12 It has been reported that GBM cells preferentially utilize glycolysis for cellular energy production, 13 and glycolysis has been targeted in a GBM stem cell model. 14 On the other hand, some authors have reported that GBM-TS primarily rely on oxidative phosphorylation, 15 and have further shown that GBM-TS survive challenge by a single agent that blocks oxidative phosphorylation by using additional metabolic pathways.…”
mentioning
confidence: 99%
“…Tumors, however, consistently rely on glycolysis even in the presence of abundant oxygen (Beckner et al, 2005;Griguer et al, 2005;Kelloff et al, 2005;Rajendran et al, 2003). Since the anaerobic metabolism of glucose to lactic acid is substantially less efficient than oxidation to CO 2 and H 2 O, tumor cells must increase glucose flux in order to maintain sufficient ATP production.…”
Section: The Warburg Effectmentioning
confidence: 99%